Malaria drug resistance: new observations and developments - Sá, Juliana M. (2011)
Drug-resistant micro-organisms became widespread in the 20th Century, often with devastating consequences, in response to widespread use of natural and synthetic drugs against infectious diseases. Antimalarial resistance provides one of the earliest examples, following the introduction of new medicines that filled important needs for prophylaxis and treatment around the globe. In the present chapter, we offer a brief synopsis of major antimalarial developments from two natural remedies, the qinghaosu and cinchona bark infusions, and of synthetic drugs inspired by the active components of these remedies. We review some contributions that early efficacy studies of antimalarial treatment brought to clinical pharmacology, including convincing documentation of atebrine-resistant malaria in the 1940s, prior to the launching of what soon became first-choice antimalarials, chloroquine and amodiaquine. Finally, we discuss some new observations on the molecular genetics of drug resistance, including delayed parasite clearances that have been increasingly observed in response to artemisinin derivatives in regions of South-East Asia.